Evaluation of Pain Pressure Threshold and Frequency of Fibromyalgia in Patients with Dysmenorrhea - Hatice Rana Erdem,; Burcu Duyur Çakıt,; Esin Çetinkaya,; Aynur Karagöz,; Meryem Saraçoğlu, (Archives of Rheumatology, 2007)
Objective: To evaluate the pain pressure threshold and the frequency of fibromyalgia syndrome (FMS) in patients with primary dysmenorrhea. Patients and Methods: Thirty-three woman with dismenorrhea (mean age 22.23±5.59 years) and age and body mass index matched 18 healthy woman were enrolled in this study. Patient and control groups were asked for common fibromyalgia symptoms such as sleep disturbances, subjective soft tissue swelling, irritabl bowel syndrome. In both groups, pain pressure threshold were measured on 18 tender points and 4 control points (thumb nail and volar side of forearm bilaterally). Total myalgic score (TMS - sum of 18 Tender Point + 4 Control Point), control point score (CPS -sum of 4 Contro Point) and mean tender point count (TPC) were calculated. Beck depression scale (BDS) was used in both groups. Results: In the dysmenorrhea group, only two patients were satisfied the diagnostic criteria of FMS (6.06%). But, widespread pain and common fibromyalgia symptoms were more frequent in the rest of the patients who had not 11/18 tender points compared to the control patients (p<0.05). In the patient and control group, the mean TMS was 136.91±19.77 and 160.15±8.81, CPS was 25.32±4.65 and 29.56±2.67, TPC was 4.54±3.44 and 1.55±1.29, respectively. The values of TMS and CPS were significantly lower and TPC was significantly higher in the patient group than control group (p<0.05). The mean pain pressure threshold value of tender point (2.97±0.72) and the mean pain pressure threshold value of all tender point and control point of the patient group were significantly lower than the mean values of the control group (3.80±0.93 and 7.58±0.41, respectively) (p<0.05). In the patient and control group the mean BDS was 20.81±8.46 and 12.88±14.33, respectively. In patient group, BDS score was significantly higher than control group (p<0.05). Conclusion: Although dysmenorrheic women didn't satisfy the diagnostic criteria of FMS, they had lower PPT values and increased frequency of fibromiyalgia symptoms. We thought that multidisciplinary treatment approach, similar to FMS treatment, may be useful in the treatment of dysmenorrhea. (Rheumatism 2007; 22: 11-4)